The effect of tropomyosin variants on cardiomyocyte function and structure that underlie different clinical cardiomyopathy phenotypes. (15th January 2021) - Dorsch, Larissa M.; Kuster, Diederik W.D.; Jongbloed, Jan D.H.; Boven, Ludolf G.; van Spaendonck-Zwarts, Karin Y.; Suurmeijer, Albert J.H.; Vink, Aryan; du Marchie Sarvaas, Gideon J.; van den Berg, Maarten P.; van der Velden, Jolanda; Brundel, Bianca J.J.M.; van der Zwaag, Paul A.
Abstract: Background – Variants within the alpha-tropomyosin gene ( TPM1 ) cause dominantly inherited cardiomyopathies, including dilated (DCM), hypertrophic (HCM) and restrictive (RCM) cardiomyopathy. Here we investigated whether TPM1 variants observed in DCM and HCM patients affect cardiomyocyte physiology differently. Methods – We identified a large family with DCM carrying a recently identified TPM1 gene variant (T201M) and a child with RCM with compound heterozygote TPM1 variants (E62Q and M281T) whose family members carrying single variants show diastolic dysfunction and HCM. The effects of TPM1 variants (T201M, E62Q or M281T) and of a plasmid containing both the E62Q and M281T variants on single-cell Ca 2+ transients (CaT) in HL-1 cardiomyocytes were studied. To define toxic threshold levels, we performed dose-dependent transfection of TPM1 variants. In addition, cardiomyocyte structure was studied in human cardiac biopsies with TPM1 variants. Results – Overexpression of TPM1 variants led to time-dependent progressive deterioration of CaT, with the smallest effect seen for E62Q and larger and similar effects seen for the T201M and M281T variants. Overexpression of E62Q/M281T did not exacerbate the effects seen with overexpression of a single TPM1 variant. T201M (DCM) replaced endogenous tropomyosin dose-dependently, while M281T (HCM) did not. Human cardiac biopsies with TPM1 variants revealed loss of sarcomeric structures. Conclusion – All TPM1 variants result in reduced cardiomyocyte CaT amplitudes and loss of sarcomeric structures. These effects may underlie pathophysiology of different cardiomyopathy phenotypes. Graphical abstract: Unlabelled Image Highlights: Role of TPM1 variants in cardiomyopathy development are relatively understudied Comprehensive clinical evaluation shows the heterogeneous cardiomyopathy phenotype First description of compound heterozygote TPM1 E62Q/M281T in a child with RCM Reduced CaT amplitudes and structural changes occur irrespective of TPM1 variants